Visions of architecture. Perspective and photographic manipulation from photomontage to rendering. - Magagnini, Marta (DISEGNARECON, 2013)
The submitted article investigates the existence of a philological and semantic continuity between contemporary perspectives made with photorealistic three-dimensional CG techniques and the analogical ones that use photography for the design process. The research, which moves from historical milestones, tracks the purposes of photomontage in architecture, form the first use in art and the in architecture, to the contemporary CG rendering. The goal is not to search for ways to construct architectural objects, but rather to use potential capability of digital design to realize the assertiveness of the image. Another issue is about the role of perspective (and the mastery of descriptive geometry) nowadays. In support of the theoretical speculations, some unedited comments by the same authors to the photomontages of Superstudio and to the renderings of Giacomo Costa.